G81(P) Bridging the gap: gp hub clinics and mdt teaching sessions. (12th March 2018) - Suri, S; Patel, D; Cooper, S; Simmonds, M
Abstract : Aims: Despite the fact that children account for 20%–25% of the caseload of GPs, training in Paediatrics is not compulsory. Public expectation is that parents should have access to specialist care immediately. Several studies have concluded that substantial numbers of children referred to secondary care can be successfully managed in primary care. These were the main drivers for setting up a GP hub clinic and Multi-disciplinary team (MDT) teaching sessions in our area. Methods: GP hub clinics were set up and evaluated over a period of 7 months between February and October 2017. Each clinic had capacity to see 5 new patients and took place every 2 weeks. An MDT session on some of these cases was undertaken every 6 weeks. Results: 10 consultant delivered clinics were held. There were 41 new appointments with 3 DNAs and 7 follow ups with 2 DNAs. The DNA rate was 7.3% for new patient slots (hospital DNA rate 14.7%) The follow up to new patient ratio was 1:1.03 (The ratio was 1: 1.56 ratio for the hospital based clinic). 2 patients were cancelled (4%) as opposed to 18% cancellation rate in hospital clinics. Overall, there was a reduction of 21% of all GP referrals (hub and non-hub clinics) in comparison to the same period in 2016. There was a reduction in referrals of 24% from the practice hosting the hub clinics. In the opinion of the consultant doing the clinic, the majority of children could have been managed in primary care with GP education (53%); GP advice and guidance (71%) or by an alternative practitioner (53%). 96% of patients were positive about the booking process, the clinic and follow up arrangements.100% of the MDT session evaluations were positive. The GPs fed back formally and informally that the resource was highly valued. Conclusion: The DNA rate and follow up to new ratio was favourable probably due to the short wait to see the consultant. Parents valued the service as it was close to home and in a familiar environment. GPs valued the MDT teaching sessions. Primary care services need to be supported by secondary care services to bring care closer to home.